Should we transfer poor quality embryos? - Kirillova, Anastasia (Fertil Res Pract, 2020)
BACKGROUND: To evaluate if it is safe and effective to transfer poor quality embryos. METHODS: It was a retrospective analysis using individual patient data with positive controls. All patients undergoing embryo transfers of poor quality embryos on day 3 or on day 5 as part of fresh In Vitro Fertilization (IVF) cycles performed between 2012 and 2016. This study assessed a total of 738 poor quality embryos from 488 IVF programs. 261 embryo transfers were performed on day 3 (402 embryos were transferred) and 227 on day 5 (336 embryos were transferred). Control group consisted of 9893 fair and good quality embryos from 5994 IVF programs. Outcome rates were compared with two-tailed Fisher exact test using fisher.test function in R software. 95% confidence intervals for proportions were calculated using the Clopper-Pearson method with binom.test function in R. The groups of patients with poor vs. good and fair quality embryos were compared by age, body mass index(BMI), number of oocytes, female and male main diagnosis, cycle type, controlled ovarian stimulation (COS) protocol, the starting day of gonadotropin administration, the starting dose of gonadotropins, the total dose of gonadotropins, the total number of days of gonadotropins administration, the starting day of gonadotropin-releasing hormone (GnRH) agonist administration, the total number of ampoules of GnRH-agonist used, day of the trigger of ovulation administration and the type of the trigger of ovulation using the Student’s t-test for interval variables and with the chi-square test for nominal variables. RESULTS: No significant differences in the implantation rate, clinical pregnancy rate, miscarriage rate, live births, and the number of children born were found between the groups of poor quality embryos transferred on day 3 and day 5. Though the implantation rate was lower for the group of poor quality embryos, than for the control (13.9% vs 37.2%), statistically significant differences between the proportion of implanted embryos which resulted in clinical pregnancies and live births in both groups were not observed (72% vs 78.2 and 55.8% vs 62.0% respectively). CONCLUSION: Transfer of poor quality embryos at either day 3 or day 5 have a low potential for implantation, though those embryos which successfully implanted have the same potential for live birth as the embryos of fair and good quality. This study supports that it is safe to transfer poor quality embryos when they are the only option for fresh embryo transfer (ET).